How to improve Marketing and Sales of Dewan Bahasa dan Pustaka (DBP) Reference Books to Institution of Higher Learning in Malaysia / Rudy Sa’edy - Sa’edy, Rudy (2002)
Publication industry in Malaysia has grown rapidly. In this industry, there are two categories, government-sponsored publications and private companies publication. These both categories plays important role in Malaysian publication industry whereby it is become more competitive and profitable.This study sought to identify the improvement of marketing and sales of DBP in the publication industry to reference books for institution of higher learning. This study also wants to identify the position of DBP books in the industry. In addition, this study also wants to find the reasons on the preferences of reference books.